Paula Coutinho’s outstanding contribution to the definition of Machado-Joseph disease - Bruno Carniatto Marques Garcia; Francisco Manoel Branco Germiniani; Paula Marques; Jorge Sequeiros; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Machado-Joseph disease, also known as spinocerebellar ataxia type 3, is the most common form of autosomal dominant ataxia in the world. Paula Coutinho, a highly-regarded Portuguese neurologist worldwide, had a seminal participation in the definition of this disease, more than 40 years ago.